Effect of river damming on nutrient transport and transformation and its countermeasures - Wang, Xun; Chen, Yu; Yuan, Qiusheng; Xing, Xiaolei; Hu, Bin; Gan, Jiawen; Zheng, Yuran; Liu, Yunxin (Frontiers in Marine Science, 2022)
In recent decades, damming has become one of the most important anthropogenic activities for river regulation, and reservoirs have become hotspots for biogeochemical cycling. The construction of dams changes riverine hydrological conditions and alters the physical, chemical, and biological characteristics of rivers, eventually leading to significant variations in nutrient cycling. This review mainly explores the effects of river damming on nutrient transport and transformation, including i) nutrient (N, P, Si, and C) retention in reservoirs, ii) greenhouse gas (GHG) emissions, and iii) interactions between the nutrient stoichiometry ratio and the health of the reservoir ecosystem. The important drivers of nutrient transport and transformation, such as river connectivity, hydraulic residence time, hydropower development mode, microbial community variation, and anthropogenic pollution, have also been discussed. In addition, strategies to recover from the negative effects of damming on aquatic ecosystems are summarized and analyzed. To provide theoretical and scientific support for the ecological and environmental preservation of river-reservoir systems, future studies should focus on nutrient accumulation and GHG emissions in cascade reservoirs.